2021
DOI: 10.1016/j.jvs.2020.10.024
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of treatment with intermittent negative pressure for intermittent claudication

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 44 publications
1
23
0
1
Order By: Relevance
“…Several studies have suggested clinical effects of INP treatment on walking distance in patients with IC [9][10][11] . In a recently published randomized controlled trial from our research group 12 , we found a significant effect of INP treatment on PWD compared to sham treatment after 12 weeks. Further, a subgroup analysis showed a significant effect on both the PWD and the MWD compared to sham treatment for the patients with the most symptomatic disease (baseline PWD<200 m) 12 .…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Several studies have suggested clinical effects of INP treatment on walking distance in patients with IC [9][10][11] . In a recently published randomized controlled trial from our research group 12 , we found a significant effect of INP treatment on PWD compared to sham treatment after 12 weeks. Further, a subgroup analysis showed a significant effect on both the PWD and the MWD compared to sham treatment for the patients with the most symptomatic disease (baseline PWD<200 m) 12 .…”
Section: Discussionmentioning
confidence: 62%
“…Post hoc tests revealed that PWD increased significantly from baseline to 12 weeks (mean 81 m; 95% CI [6,156]; p=0.032), but there was no significant change in PWD from 12…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations